THE EFFECTS OF TEACHING MEDIA AND SENTENCE STRUCTURE MASTERY TOWARDS STUDENTS’ WRITING SKILLS IN DESCRIPTIVE TEXT - Asuroh, Asuroh (Jurnal Gemaedu, 2016)
The aim of the research is to knowThe effect of teaching media and sentence structure mastery towards students’ writing skills descriptive text. The research methodology that is used experimental research. The population of this research was all students in the eight grade State Junior High School Cibinong. Sample taken in this research is 2 classes that are become 2 groups, consists of 30 students. So each group consists of 30 students. 30 students with picture teaching media 30 with conventional technique. The research findings are: 1) There is any significant effect of Teaching Media towards Students’ Writing Skills in Descriptive Text at State Junior High Schools at Cibinong. That is proved by sig value  = 0.000 < 0.05. It means that there is significance different of Student’s Writing Skills in Descriptive Text  of the students who are taught by  The Picture Media  and Student’s Writing Skills in Descriptive Text  who are taught by Conventional Teaching. 2) There is any significant effect of Sentence Structure Mastery towards Students’ Writing Skills in Descriptive Text  at State Junior High Schools at Cibinong. That is proved by sig value = 0.000 < 0.05. It means that there is significance difference of Student’s Writing Skills in Descriptive Text of the students whose High Sentence Structure Mastery with Student’s Writing Skills in Descriptive Text of the students whose Low Sentence Structure Mastery. 3) There are significant interactive effects of Teaching Media  and Sentence Structure Mastery towards Students’ Writing Skills in Descriptive Text  at State Junior High Schools at Cibinong. That is proved by sig value  = 0.039 < 0.05.